Sistematización de la creación colectiva del juego coreográfico “Colombia Descabezada” (2021)
The objective of this work is to systematize the pedagogical process and the creation of pedagogical practice III carried out in the first semester of 2021 with the elderly group of the house of culture in Mosquera Cundinamarca. The process consisted of an investigation into the collective costume "El Descabezado" which participates in the Barranquilla Carnival, and later a space for collective creation was developed that gave as a final product the choreographic game called "Colombia Descabezada", a work that was circulated in the 2021-1 semester samples through the YouTube audiovisual platform.